Climate in some stations of the Atlantic Zone of Costa Rica - Herrera Reyes, C.G.; Jansen, D.M. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
25 pág, 2 ilus, 10 tab, 9 ref. También como: Field Report - Atlantic Zone Programme (CATIE) no. 125